Epidemiology and Trends of Infective Meningitis in Neonates and Infants Less than 3 Months Old in Hong Kong. (October 2021) - Wong, Chi Hang; Duque, Jaime Rosa; Wong, Joshua Sung Chih; Chan, Chi-man Victor; Lam, Cheuk San Ivan; Fu, Yu Ming; Cheong, Kai-Ning; Chua, Gilbert T.; Lee, Pamela P.; Ip, Patrick; Ho, Marco Hok Kung; Wong, Ian Chi Kei; et al.
Highlights: Group B Streptococcus (GBS) and Escherichia coli remain the most common causes of meningitis in neonates and young infants GBS screening and intrapartum antibiotic prophylaxis were effective in preventing early-onset GBS meningitis Antibiotic-resistant Escherichia coli in neonatal meningitis is an increasing concern Abstract: Objectives: Meningitis in neonates and young infants leads to significant morbidity and mortality worldwide. This study aimed to investigate pathogens, antibiotic resistance and secular change of incidence in Hong Kong. Methods: A retrospective search was performed on meningitis in neonates and infants aged <3 months in three Hong Kong public hospitals from 2004 to 2019. Medical charts were reviewed, with focus on the identification and antibiotic resistance of the pathogens. Results: A total of 200 cases of meningitis were identified (67% were bacterial). Group B Streptococcus (GBS) and Escherichia coli ( E. coli ) were the commonest bacterial pathogens. The annual rates of early-onset GBS meningitis decreased after the implementation of universal GBS screening and intrapartum antibiotic prophylaxis (IAP) in 2012, while that of late-onset GBS meningitis remained similar. A significant portion of E. coli isolates were resistant to ampicillin and/or gentamicin. Conclusion: GBS and E. coli were the most common bacteria for meningitis in this age group. The annual rate of bacterial meningitis in Hong Kong has declined in recent years, which has been attributed to the decline in early-onset GBS meningitis due to universal GBS screening and IAP. Antimicrobial-resistant bacterial strains that cause meningitis require further clinical and public health attention.